2021
DOI: 10.1111/1471-0528.16741
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on the Ontario Cervical Screening Program, colposcopy and treatment services in Ontario, Canada: a population‐based study

Abstract: Objective: To describe the immediate impact of the COVID-19 pandemic on cervical screening, colposcopy and treatment volumes in Ontario, Canada. Design: Population-based retrospective observational study Setting: Ontario, Canada Population: People with a cervix age 21 to 69 years who completed at least one cervical screening cytology test, colposcopy or treatment procedure for cervical dysplasia between January 2019 and August 2020. Methods: Administrative databases were used to compare cervical screening cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 11 publications
2
44
0
6
Order By: Relevance
“…2 Some backlogs persisted, with 33% of Ontarians with high-grade screening cervical cytology results before the start of the pandemic still awaiting colposcopy as of August 2020. 6 Patients living in neighbourhoods in the lowest income quintile were more likely to have diagnostic delays following an abnormal breast, colorectal, or cervical screening result than were those in higher-income neighbourhoods. 2 Patient hesitancy to be seen in person, coupled with the rise of virtual care and decreased health care resources for diagnosis, including biopsy and imaging, reduced the number of symptomatic cancers diagnosed.…”
Section: Impacts On Cancer Screening and Diagnosismentioning
confidence: 94%
“…2 Some backlogs persisted, with 33% of Ontarians with high-grade screening cervical cytology results before the start of the pandemic still awaiting colposcopy as of August 2020. 6 Patients living in neighbourhoods in the lowest income quintile were more likely to have diagnostic delays following an abnormal breast, colorectal, or cervical screening result than were those in higher-income neighbourhoods. 2 Patient hesitancy to be seen in person, coupled with the rise of virtual care and decreased health care resources for diagnosis, including biopsy and imaging, reduced the number of symptomatic cancers diagnosed.…”
Section: Impacts On Cancer Screening and Diagnosismentioning
confidence: 94%
“…A 94% drop in cervical screening was reported in May 2020 in the US with a catch-up programme seen as a priority. 11 A 63.8% decrease of cervical cytology screening tests was reported in Ontario 12 and an 82% drop was reported in the gynaecological cytology workload in the Asia-Pacific region. 13 The authors stressed the importance of effective laboratory biosafety protocols which may have an impact on the capacity for testing.…”
Section: Af Ter the Paus Ementioning
confidence: 99%
“…A 94% drop in cervical screening was reported in May 2020 in the US with a catch‐up programme seen as a priority 11 . A 63.8% decrease of cervical cytology screening tests was reported in Ontario 12 and an 82% drop was reported in the gynaecological cytology workload in the Asia‐Pacific region 13 …”
Section: After the Pausementioning
confidence: 99%
“…Although cancer treatment has been guaranteed during the COVID‐19 pandemic, screenings have been suspended and/or severely reduced worldwide during the first and second waves due to the reprioritisation of health services, 1 as was clearly highlighted by Meggetto et al. 2 In a report about a cervical screening programme in Ontario, recent data on the effect of screening discontinuation during the first wave demonstrated increased delays in cancer diagnosis and treatment. Notably, population‐based studies reported a 30% reduction in primary care consultations and a 12–15% reduction in the number of referrals for both colorectal and breast cancer, with a significant increase in more advanced stages of disease compared with the same period in 2019.…”
mentioning
confidence: 99%
“…Notably, population‐based studies reported a 30% reduction in primary care consultations and a 12–15% reduction in the number of referrals for both colorectal and breast cancer, with a significant increase in more advanced stages of disease compared with the same period in 2019. 2 , 3 …”
mentioning
confidence: 99%